2019
DOI: 10.1007/s00227-019-3472-x
|View full text |Cite
|
Sign up to set email alerts
|

Ecohydrographic control on the community structure and vertical distribution of pelagic Chaetognatha in the Red Sea

Abstract: 31The present study details the effects of basin-scale hydrographic characteristics of the Red Sea 32 on the macroecology of Chaetognatha, a major plankton component in the pelagic realm. The 33 hydrographic attributes and circulation of the Red Sea as a result of its limited connection with 34 the northern Indian Ocean make it a unique ecohydrographic region in the world ocean. Here, we 35 aimed to identify the prime determinants governing the community structure and vertical 36 distribution of the Cheatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 44 publications
2
8
1
Order By: Relevance
“…In contrast, siphonophores showed no lagged correlation with environmental variables, which were generally weak. The weak relationship between siphonophore abundance and environmental properties is consistent with previous reports in the Red Sea for Chaetognatha (Cornils et al, 2007;Karati et al, 2019), and may result from their trophic dependence on copepods and other small heterotrophic organisms. The abundance of siphonophores may have also been affected by the input of allochthonous organic matter with dust deposition events (Jish Prakash et al, 2015;Rushdi et al, 2019), which can stimulate the growth of small zooplanktonic prey FIGURE 4 | A summary of (A) seasonal blooming dynamics of main groups gelatinous zooplankton taxa (i.e., tunicates, siphonophores, Ulmaridae) and relative dynamics of temperature ( • C) and chlorophyll a (µg L −1 ) found during the study period, and (B) rapid short-term fluctuations showed by Porpitidae and relative dynamics of temperature ( • C) over the study period.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In contrast, siphonophores showed no lagged correlation with environmental variables, which were generally weak. The weak relationship between siphonophore abundance and environmental properties is consistent with previous reports in the Red Sea for Chaetognatha (Cornils et al, 2007;Karati et al, 2019), and may result from their trophic dependence on copepods and other small heterotrophic organisms. The abundance of siphonophores may have also been affected by the input of allochthonous organic matter with dust deposition events (Jish Prakash et al, 2015;Rushdi et al, 2019), which can stimulate the growth of small zooplanktonic prey FIGURE 4 | A summary of (A) seasonal blooming dynamics of main groups gelatinous zooplankton taxa (i.e., tunicates, siphonophores, Ulmaridae) and relative dynamics of temperature ( • C) and chlorophyll a (µg L −1 ) found during the study period, and (B) rapid short-term fluctuations showed by Porpitidae and relative dynamics of temperature ( • C) over the study period.…”
Section: Discussionsupporting
confidence: 91%
“…However, the presence of dust or smaller planktonic organisms such as Synechococcus, Prochlorococcus, Eukariots and Bacteria, did not show any relationship in our multivariate or univariate exploratory analysis. Even though not captured in our study, these trophic dependences could have contributed to the uncoupling of this zooplanktonic component to environmental factors (e.g., temperature, salinity; Boero et al, 2008;Al-Aidaroos et al, 2016;Karati et al, 2019). Lastly, the occurrence of larger taxa (i.e., particularly Ulmaridae) appears difficult to explain with local factors, and may be dependent on processes occurring at larger spatial and temporal scales (Bastian et al, 2011;Canepa et al, 2013).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The POC flux just below the productive layer ( Ezp) was lower than those reported in other areas of the global ocean except for the eastern part of the Mediterranean Sea (Figure 10c). Recent studies showed that most of the biomass of zooplankton in the Red Sea is mainly found in the upper layer of the water column (0–100 m) due to the presence of low oxygenated waters below 100 m (Karati et al, 2019). The scenario of low abundance of mesozooplankton in Red Sea waters may explain these differences.…”
Section: Discussionmentioning
confidence: 99%